Capital control regime and capital structure determinants : a Malaysian case / Mohd Nazam Dzolkarnaini - Dzolkarnaini, Mohd Nazam (Faculty of Accountancy & Accounting Research Institute (ARI), 2006)
In light of 1997 Asian crisis, the adoption of capital control regime by Malaysian government on 1st September 1998 is very much controversial. Despite being highly criticised, it is argued that Malaysia has recovered nicely On 21st July 2005, the government announced the scrapping of the seven-year old ringgit's peg to the US dollar. As ringgit depegging marks a significant upliftment of one of the capital control policies, an early assessment of the policies' effectiveness is timely. This paper examines the impact of capital control on the leverage ratios of Malaysian companies during the period 1st September 1994 - 31st August 2002. Further, the paper investigates the issues of capital control and the capital structure determinants. Results indicate that (i) the capital control has significantly changed the overall leverage ratios between the pre and the post-capital control periods; (ii) the leverage level of Malaysian companies is mainly driven by three major factors, namely the company size, the profitability and the liquidity; and (Hi) the capital control has a significant impact on the role of some capital structure determinants. With all these evidence, it is suggested that the capital control adoption is proven successful in stabilising the economy, at least in the medium-term.